НАЦІОНАЛЬНІ МЕНШИНИ В ТИПОЛОГІЇ СЕЛЯНСЬКОГО ПОВСТАНСЬКОГО РУХУ ПІВДНЯ УКРАЇНИ (Zaporizhzhia Historical Review, 2021)
The article (on the basis of archival sources) discusses the role of ethnical representatives in insurgent movement of the population of the South of Ukraine. It is ascertained, that the factor of national minorities participation in insurgent movement is a little-studied stage of Ukrainian history.